A questão da disciplina na escola: percepções dos estudantes do 5º ano no ensino fundamental - Tomasella, Simone Fernanda Teixeira (Universidade Federal de São Carlos, 2023)
The foundation of modern education, as it was described by Enlightenment ideals, gives man the condition to think for himself. The pedagogy, which emerges from this context, has as its purpose the formation of the subject's moral autonomy. Immanuel Kant (1724-1804) was an illustrious German philosopher recognized as one of the main representatives of the intellectual movement known as Enlightenment. Among his contributions in various areas of philosophy, Kant also showed great concern with the educational issues of his time, placing us in front of one of the biggest problems of education, which is the possibility of reconciling subjugation to the coercion of laws with the ability to serve freedom. Undoubtedly, this problem remains an important challenge in the field of education. In the contemporary analysis of Adorno and Horkheimer, the Enlightenment Reason, developed by the bourgeoisie at the beginning of the modern era, overshadowed the dream of an emancipatory freedom. Given its contributions to thinking about education today, this research aims to analyze the students' perception of discipline at school, in order to promote a discussion about the relationship between discipline, authority and freedom in the current school context from the perspective of positioning of 5th grade students in Elementary School. The research proposes an empirical study with a mixed approach of a qualitative and quantitative nature, having bibliographic research and field research as a methodological reference, with the application of a form involving items from a Likert-type scale containing statements about the discipline, in view of to analyze the level of agreement and frequency attributed by students of the 5th year of Elementary School, to the affirmations of these attitudes. It is imperative, therefore, to take a look at the student who attends school today. In this sense, it is important to articulate these aspects with the studies of some contemporary theorists who think about the current school and discuss the relationship of the discipline linked to the mechanisms of control, didactics, violence, domestication, authoritarianism, moralism, among other coercive practices to deal with the problem of discipline, thus seeking to understand the formation process of the moral autonomy of human beings.
The issue of discipline at school: perceptions of 5th year students in elementary school
Keywords: Disciplina; Autoridade; Autonomia moral; Teoria Crítica da Sociedade; Discipline; Authority; Moral autonomy; Critical Theory of Society; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO